Precisiones sobre el vocabulario de la ciencia en Roma: criterios de identificación y análisis de los términos geométricos en latín - Ayuso García, Manuel; Moreno Hernández, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
As is well known, an outstanding improvement has recently become in the study of the scientific and technical fields of Latin lexicon. However, it is necessary to set up clearly the criteria in order to identify and analyse the terms in Latin according to the progress reached by terminology as an autonomous science, specially in the last decades. The object of this article is to put forward an approach to these criteria in a specialized field like Geometry in Latin language. We suggest some criteria to determine when a word can be considered a term in this field, in what conditions it is used and in which discursive contexts. These criteria could be extended as well to other different Latin terminological fields.